Fabrication of Co/P25 coated with thin nitrogen-doped carbon shells (Co/P25/NC) as an efficient electrocatalyst for oxygen reduction reaction (ORR). (10th February 2019) - Miyake, Koji; Takemura, Toshiki; Gabe, Atsushi; Zhu, Yexin; Ota, Misaki; Shu, Yasuhiro; Hirota, Yuichiro; Uchida, Yoshiaki; Tanaka, Shunsuke; Katayama, Misaki; Inada, Yasuhiro; Morallón, Emilia; et al.
Abstract: Development of electrocatalysts for oxygen reduction reaction (ORR) is important to solve the current problems about energy and fuel. As one of the catalysts with high performance, platina group metals (PGM) based catalysts have been widely known. However, PGM based catalysts are not suitable for large commercial application since the PGM based catalysts are so expensive. In this work, we have developed TiO2 P25 coated with Co and nitrogen-doped carbon layers using commercially available and inexpensive P25 as a support (Co/P25/NC) as one of the alternatives to PGM based catalysts. Co/P25/NC showed an excellent catalytic activity on ORR compared to the other catalysts prepared using SiO2, ZrO2 and Al2 O3 as a support. The ORR activity of Co/P25/NC was comparable to Pt based electrocatalysts. In addition, Co/P25/NC showed excellent durability and tolerance toward methanol compared to the Pt based catalyst. This work would provide a new synthetic strategy of electrocatalysts.